2008
DOI: 10.1080/10236190701698155
|View full text |Cite
|
Sign up to set email alerts
|

Planar maps whose second iterate has a unique fixed point

Abstract: Let ǫ > 0, F : R 2 → R 2 be a differentiable (not necessarily C 1 ) map and Spec(F ) be the set of (complex) eigenvalues of the derivative DF p when p varies in R 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…In the appendix of [7] it is shown that the eigenvalues of DF 4 (x, y) lie in the open unit disk, establishing 5). Statement 3) follows as a direct consequence of Corollary 2 in [2] and the same estimates on the eigenvalues.…”
Section: Example With An Orbit Of Periodmentioning
confidence: 67%
“…In the appendix of [7] it is shown that the eigenvalues of DF 4 (x, y) lie in the open unit disk, establishing 5). Statement 3) follows as a direct consequence of Corollary 2 in [2] and the same estimates on the eigenvalues.…”
Section: Example With An Orbit Of Periodmentioning
confidence: 67%
“…In many contexts, this condition is simply known as f is dissipative, see for instance [3]. The fourth is not really a condition, it is a consequence of the previous ones, as shown by Corollary 2 of [2].…”
Section: Point At Infinity Is a Repeller;mentioning
confidence: 91%
“…The issue of uniqueness of a fixed point has been addressed by Alarcón et al [4] who gave simple conditions for planar maps under which the origin is the unique fixed point.…”
Section: Introductionmentioning
confidence: 99%